Multiple house occupancy is associated with mortality in hospitalized patients with COVID-19. (17th May 2021) - Bruce, Eilidh; Carter, Ben; Quinn, Terence J; Verduri, Alessia; Pearson, Oliver; Vilches-Moraga, Arturo; Price, Angeline; McGovern, Aine; Evans, Louis; McCarthy, Kathryn; Hewitt, Jonathan; Moug, Susan; et al.
Abstract: Background: In response to the COVID-19 pandemic, many countries mandated staying at home to reduce transmission. This study examined the association between living arrangements (house occupancy numbers) and outcomes in COVID-19. Methods: Study population was drawn from the COPE study, a multicentre cohort study. House occupancy was defined as: living alone; living with one other person; living with multiple other people; or living in a nursing/residential home. Outcomes were time from admission to mortality and discharge (Cox regression), and Day 28 mortality (logistic regression) analyses were adjusted for key comorbidities and covariates including admission: age, sex, smoking, heart failure, admission C-reactive protein (CRP), chronic obstructive pulmonary disease, estimated glomerular filtration rate, frailty and others. Results: A total of 1584 patients were included from 13 hospitals across UK and Italy: 676 (42.7%) were female, 907 (57.3%) were male, median age was 74 years (range: 19–101). At 28 days, 502 (31.7%) had died. Median admission CRP was 67, 82, 79.5 and 83 mg/l for those living alone, with someone else, in a house of multiple occupancy and in a nursing/residential home, respectively. Compared to living alone, living with anyone was associated with increased mortality: within a couple [adjusted hazard ratios (aHR) = 1.39, 95% confidence intervals (CI) 1.09–1.77, P  = 0.007]; living in a house of multiple occupancy (aHR = 1.67, 95% CI 1.17–2.38, P  = 0.005); and living in a residential home (aHR = 1.36, 95% CI 1.03–1.80, P  = 0.031). Conclusion: For patients hospitalized with COVID-19, those living with one or more people had an increased association with mortality, they also exhibited higher CRP indicating increased disease severity suggesting they delayed seeking care.